Preparation, characterization and biological studies of β-TCP and β-TCP/Al2O3 scaffolds obtained by gel-casting of foams - Siqueira, Lilian; De Paula, Cynthia Guimarães; Motisuke, Mariana; Gouveia, Rubia Figueredo; Camargo, Samira Esteves Afonso [UNESP]; Milhan, Noala Vicensoto Moreira [UNESP]; De Sousa Trichês, Eliandra (FapUNIFESP (SciELO), 2017)
Replacement tissues for tissue engineering can be produced by seeding human cells onto scaffolds. In order to guarantee adequate bio-compatibility, porosity and mechanical resistance for promoting cellular growth, proliferation and differentiation within scaffold structures, it is necessary to investigate and improve materials and processing routes. β-tricalcium phosphate can be considered a very suitable bio-ceramic material for bone therapy because of its biocompatibility, osteo-conductivity and neovascularization potential. Alumina is commonly used as a sintering additive. In this study, β-TCP and β-TCP/Al2O3 scaffolds were obtained by gel-casting method. The scaffolds showed high porosity (86- 88%) and pore sizes ranging from 200 to 500 μm. Even though alumina did not promote improvement in β-TCP/Al2O3 scaffolds in terms of mechanical performance, they showed great cytocompatibility as there was no cytotoxic and genotoxic effect. Therefore, β-TCP and β-TCP/Al2O3 scaffolds are good candidates for application in tissue engineering.
Keywords: Alumina; Cytocompatibility; Gel-casting method; Scaffolds; Tricalcium phosphate